Legal Protection of Human Rights Against Victims of Trafficking in Persons - Indri Afnita Mars; Joko Setiyono (Jurnal Multidisiplin Madani, 2023)
Human trafficking, according to Article 1 (1) of Law Number 21 of 2007 concerning Eradication of Crime Against Persons, is trafficking in persons as an act of obtaining, transferring, hiding, sending, transferring, or receiving someone with threats of violence, use . by force, kidnapping, imprisonment, forgery, fraud, abuse of power or weakness, bondage or for exploitation or creating people. All forms of trafficking in women and children are violations of human rights, children's rights and labour rights, which treat victims as usual goods bought, sold, shipped and resolved. Its constant complexity is simply the operating conditions it places on people. The protections offered to victims of human trafficking are restitution, compensation, rehabilitation and reintegration. Protection of victims is, in principle, intended to overcome the consequences felt by the victim due to the crime committed against the person concerned. The human right of trafficking in persons must b at the core of all efforts to prevent and combat trafficking in persons and to protect, assist and compensate